(untitled) (Itinerarios Educativos, 2024)
This article presents part of the results of a completed research project, financed with funds from the National Institute for Teacher Training (INFoD) in the 2021 Call for Teacher Training Institutes throughout the country. In this project we proposed to analyze the classes written and published in the virtual classrooms of a teacher training institute (IFD) in the city of Córdoba, as well as the writing process of these by teachers and their reception by the students during 2020 and 2021. In this article we seek to socialize the results of the first phase of this research, which addresses the discourse analysis of virtual classrooms: first, we present the discourse analysis model built to respond to this phase and then we share some results of this analysis in the form of a classification arising from the interpretive work.We believe that the analysis model itself can be a useful tool for other investigations, but it can also guide the teaching production of new classes in virtual classrooms.